2022
DOI: 10.1039/d2nj00324d
|View full text |Cite
|
Sign up to set email alerts
|

Successful CO2 reduction under visible light photocatalysis using porous NiO nanoparticles, an atypical metal oxide

Abstract: An efficient wet chemical one-pot synthesis strategy for the preparation of NiO nanoparticles has been reported. The nano-structured NiO has surface bound hexamine and it has emerged as a proficient...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Studies on the mitigation and use of CO 2 are being conducted in various applications such as metal-and nanomaterials-fused electrochemical catalysis, photocatalysis, and biological catalysis [13][14][15]. Among these, Carbon dioxide (CO 2 ) is the most abundant component of greenhouse gases (GHGs) and directly creates environmental issues such as global warming and climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the mitigation and use of CO 2 are being conducted in various applications such as metal-and nanomaterials-fused electrochemical catalysis, photocatalysis, and biological catalysis [13][14][15]. Among these, Carbon dioxide (CO 2 ) is the most abundant component of greenhouse gases (GHGs) and directly creates environmental issues such as global warming and climate change.…”
Section: Introductionmentioning
confidence: 99%
“…A great number of photocatalysts, for example, metal oxides, metal sulfide, organic polymers, metal organic frameworks, and covalent organic frameworks, have been developed to catalyze the conversion of CO 2 to hydrocarbon fuels. [15][16][17][18] Organic polymer carbon nitride (g-CN) is attracting increasing attention since Wang et al found its application in photocatalysis hydrogen evolution. 19,20 In the past few years, g-CN has been widely studied in the field of photocatalysis CO 2 reduction due to its suitable band gap for visible light absorption, strong redox ability, low costs, and ecofriendly properties.…”
Section: Introductionmentioning
confidence: 99%